One‐Day Versus Three‐Day Dexamethasone in Combination with Palonosetron for the Prevention of Chemotherapy‐Induced Nausea and Vomiting: A Systematic Review and Individual Patient Data‐Based Meta‐Analysis. (19th June 2019) - Okada, Yuki; Oba, Koji; Furukawa, Naoto; Kosaka, Yoshimasa; Okita, Kenji; Yuki, Satoshi; Komatsu, Yoshito; Celio, Luigi; Aapro, Matti
Abstract: Background: A dexamethasone‐sparing regimen consisting of palonosetron plus 1‐day dexamethasone for the prevention of chemotherapy‐induced nausea and vomiting (CINV) has been studied previously. Here, we evaluate the noninferiority of the dexamethasone‐sparing regimen in overall antiemetic control using a meta‐analysis based on individual patient data (IPD). Materials and Methods: We conducted a systematic review for randomized trials reporting CINV outcomes for the comparison of palonosetron plus 1‐day dexamethasone (d1 arm) versus the same regimen followed by dexamethasone on days 2–3 after chemotherapy (d3 arm) in chemotherapy‐naïve adult patients undergoing either moderately emetogenic chemotherapy (MEC) or anthracycline plus cyclophosphamide (AC)‐containing chemotherapy. PubMed and MEDLINE were searched electronically. A manual search was also conducted. The primary endpoint was complete response (CR; no emesis and no rescue medication) in the overall 5‐day study period. The noninferiority margin was set at −8.0% (d1 arm−d3 arm). Results: Five studies ( n = 1, 194) were eligible for analysis and all IPD was collected. In the overall study period, the d1 arm showed noninferiority to the d3 arm for CR as well as complete control (pooled risk difference in CR rate − 1.5%, 95% confidence interval [CI] −7.1 to 4.0%, I 2 = 0%; in complete control rate − 2.4%, 95% CI −7.7 to 2.9%, I 2 = 0%). There was no significant interaction between dexamethasone regimen and risk factors (type of chemotherapy, sex, age, and alcohol consumption). Conclusion: This IPD meta‐analysis indicates that the dexamethasone‐sparing regimen is not associated with a significant loss in overall antiemetic control in patients undergoing MEC or AC‐containing chemotherapy, irrespective of known risk factors for CINV. Implications for Practice: Although dexamethasone in combination with other antiemetic agents has been used to prevent chemotherapy‐induced nausea and vomiting (CINV), it is of clinical importance to minimize total dose of dexamethasone in patients undergoing multiple cycles of emetogenic chemotherapy. This individual‐patient‐data meta‐analysis from five randomized controlled trials (1, 194 patients) demonstrated a noninferiority of the dexamethasone‐sparing regimen for complete response and complete control of CINV. The outcomes were comparable across patients with different characteristics. These findings thus help physicians minimize use of the steroid and further reduce the burden of dexamethasone‐related side effects in patients undergoing multiple consecutive courses of emetogenic chemotherapy. Abstract : Chemotherapy‐induced nausea and vomiting are common adverse effects associated with the use of cytotoxic chemotherapy drugs. This article evaluates differences in complete response rates and other antiemetic outcomes in dexamethasone‐spacing regimens.